Older doctors and progression through specialty training in the UK: a cohort analysis of General Medical Council data. Issue 2 (3rd February 2015) - Pyne, Yvette; Ben-Shlomo, Yoav
Abstract : Objective: To determine whether older age at graduation is associated with any difference in outcomes from the annual specialty training progression assessment. Design: An open cohort of 38 308 doctors who graduated from a UK medical school with annual assessments of progression in their specialty training programme with data centrally collected by the General Medical Council between 5 August 2009 to 31 July 2012. Results: Mature junior doctors (≥29 years at graduation) were more likely to have problems with progression on their annual review of competence progression record of in training assessment (ARCP/RITA) than their younger colleagues (OR 1.34, 95% CI 1.22 to 1.49, p<0.001). This association was, if anything, even stronger (OR 1.57, 95% CI 1.41 to 1.74, p<0.001) after adjustment for gender, ethnicity, type of University and specialty. The same was true when only looking at the most extreme ARCP outcome (4) which is being asked to leave their specialist programme (OR 1.81, 95% CI 1.34 to 2.44, p<0.001). Conclusions: Mature doctors are a growing part of the medical workforce and they are likely to broaden the spectrum of doctors by bring different life experience to the profession. These results suggest that they are more likely to have problems with progressing through their specialist training programme. More research is required to determine the reasons behind these associations and how mature doctors can be supported both in choosing the best training programme and in coping with the complex demands of higher training at a later stage in their lives.